Ion Exchange Study of Some New Copolymer Resins Derived from 8-Hydroxyquinoline-5-sulphonic Acid, Biuret and Formaldehyde - P. A. Dhakite; W. B. Gurnule (E-Journal of Chemistry)
Copolymer resins (8-HQSABF) were synthesized by the condensation of 8-hydroxyquinoline-5-sulphonic acid and biuret with formaldehyde in the presence of hydrochloric acid as catalyst, proved to be selective chelation ion exchange copolymer resins for certain metals. Chelation ion exchange properties to these polymers were studied for Cu2+, Cd2+, Co2+ and Zn2+ ions. A batch equilibrium method was employed in the study of the selectivity of the distribution of a given metal ions between the polymer sample and a solution containing the metal ion. The study was carried out over a wide pH range and in a media of various ions strengths. The polymer showed a higher selectivity for Cu2+ ions than for Cd2+, Co2+ and Zn2+ ions. Hence on the basis of above studies these copolymer may be used as semiconductors, surface coating, ion-exchangers, materials for rechargeable battery cell in various electronic industries, plastic materials, elastomers and in boiler plants